piggyBac-based insertional mutagenesis in the presence of stably integrated P elements in Drosophila. - Hacker, U.; Nystedt, S.; Barmchi, M.P.; Horn, C.; Wimmer, E.A. (Proceedings of the National Academy of Sciences of the United States of America, 2003)
P element-mediated mutagenesis has been used to disrupt an estimated 25% of genes essential for Drosophila adult viability. Mutation of all genes in the fly genome, however, poses a problem, because P elements show significant hotspots of integration. In addition, advanced screening scenarios often require the use of P element-based tools like the generation of germ-line mosaics using FLP recombinase-mediated recombination or gene misexpression using the UAS/Gal4 system. These techniques are P element-based and can therefore not be combined with the use of P elements as mutagenic agents. To circumvent these limitations, we have developed an insertional mutagenesis system using non-P element transposons. An enhanced yellow fluorescent protein-marked piggyBac-based mutator element was mobilized by a piggyBac specific transposase source expressed from a Hermes-based jump-starter transposon marked with enhanced cyan fluorescent protein. In a pilot screen, we have generated 798 piggyBac insertions on FRT bearing third chromosomes of which 9% have sustained a putatively piggyBac-related lethal hit. The FRTs present on the target chromosome remained stably integrated during the screen and could subsequently be used to generate germ-line clones associated with maternal and zygotic phenotypes. PCR-based analysis of insertion loci shows that 57% of the insertions are in genes for which no P element insertions have been reported. Our data demonstrate the potential of this technique to facilitate the quest for saturation mutagenesis of the Drosophila genome. The system is Drosophila nonspecific and potentially applicable in a broad spectrum of nonmodel organisms.